Learning educational institutions and information technology - Andziulienė, Beatričė; Brauklytė, Ilona (Lietuvos matematikos rinkinys, 2004)
Seeking to improve the quality of the provided knowledge for the students in an educational institution, the processes of knowledge creation, reception, application, implementation, accumulation and spread have to be managed. The proceeding of these processes has to be ensured both, in the inside and outside of the organization, applying the modern information technologies and knowledge of management, i.e. following the development route of the learning organization, which will highlight the higher educational institutions in the knowledge economics.Grounded on the conception of the learning organization, the article analyses the link between information technologies and organizational learning. The site research results of the Lithuanian higher educational institutions in the openness for the society are presented. The application of modern communicational tools for the relation with the outer environment are discussed. The present situation and the perspectives of the electronic public services supply in the educational institutions are analysed.
Keywords: learning organization; information technology; organization learning; electronic public facility